Cerebrospinal Fluid in a Small Cohort of Patients with Multiple Sclerosis Was Generally Free of Microbial DNA - Jovel, Juan; O'keefe, Sandra; Patterson, Jordan; Bording-Jorgensen, Michael; Wang, Weiwei; Mason, Andrew L.; Warren, Kenneth G.; Wong, Gane Ka-Shu (Frontiers in Cellular and Infection Microbiology, 2017)
Multiple sclerosis (MS) is a common cause of non-traumatic neurologic disability with high incidence in many developed countries. Although the etiology of the disease remains elusive, it is thought to entail genetic and environmental causes, and microbial pathogens have also been envisioned as contributors to the phenotype. We conducted a metagenomic survey in cerebrospinal fluid (CSF) from 28 MS patients and 15 patients suffering other type of neurological conditions. We detected bacterial reads in eight out of the 15 non-MS patients and in a single MS patient, at an abundance > 1% of total classified reads. Two patients were of special interest: one non-MS patient harbored 73% bacterial reads, while an MS patient had 83% bacterial reads. In the former case, Veillonella parvula, a bacterium occasionally found associated with meningitis was the predominant species, whilst Kocuria flava, apparently an environmental bacterium, predominated in the latter case. Thirty-four out of 43 samples contained less than 1% bacterial reads, which we regard as cross- or environmental contamination. A few viral reads corresponding to Epstein-Barr virus, cytomegalovirus and parvovirus were also identified. Our results suggest that CSF of MS patients is often (but not always) free of microbial DNA.